(untitled) (Research, Society and Development, 2022)
This study identified the functions of the Brazilian female volleyball supervisor, to characterize and delimit the position and its hierarchical area of ​activity, and consequently, to identify its importance for the team. The qualitative approach was adopted, with an exploratory and descriptive objective, using content analysis applied to interviews with two subjects. The first was, the supervisor of the Brazilian women’s volleyball team, an unstructured interview with a heuristic function. The second was 5 supervisors from the best teams placed in the 2017/2018 Women’s Super League, with a semi-structured interview. The analysis of the first subject identified the responsibilities of the supervisor as logistical functions, materials management, communication, people, and financial management. The analysis of the second subject obtained confirmation of the above functions and a new one, risk management. It is concluded that the supervisor is a manager at the operational level, who needs to have knowledge and responsibilities in the management functions.